1998
DOI: 10.1126/science.280.5361.275
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Intestinal T Cells from Progenitors Residing in Gut Cryptopatches

Abstract: Cryptopatches (CPs) are part of the murine intestinal immune compartment. Cells isolated from CPs of the small intestine that were c-kit positive (c-kit+) but lineage markers negative (Lin-) gave rise to T cell receptor (TCR) alphabeta and TCR gammadelta intestinal intraepithelial T cells after in vivo transfer or tissue engraftment into severe combined immunodeficient mice. In contrast, cells from Peyer's patches and mesenteric lymph nodes, which belong in the same intestinal immune compartment but lack c-kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
196
1
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 276 publications
(201 citation statements)
references
References 14 publications
1
196
1
3
Order By: Relevance
“…Recently, however, we identified multiple tiny clusters (ϳ1500) filled with ϳ1000 c-kit ϩ IL-7R ϩ Thy-1 ϩ lympho-hemopoietic progenitors in crypt lamina propria (LP) of the mouse small intestine (cryptopatches; CP) (26) and corroborated that c-kit ϩ Lin Ϫ (Lin; CD3, B220, Mac-1, Gr-1, and TER119) cells separated by flow cytometry from CP cells were capable of reconstituting ␣␤-and ␥␦-IEL in irradiated SCID mice (27). In contrast, cells from Peyer's patches (PP) and mesenteric lymph nodes (MLN), which belong in the same intestinal immune compartment but lack c-kit ϩ Lin Ϫ cells, failed to do so.…”
Section: N Umerous Intraepithelial T Cells (Iel)mentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, however, we identified multiple tiny clusters (ϳ1500) filled with ϳ1000 c-kit ϩ IL-7R ϩ Thy-1 ϩ lympho-hemopoietic progenitors in crypt lamina propria (LP) of the mouse small intestine (cryptopatches; CP) (26) and corroborated that c-kit ϩ Lin Ϫ (Lin; CD3, B220, Mac-1, Gr-1, and TER119) cells separated by flow cytometry from CP cells were capable of reconstituting ␣␤-and ␥␦-IEL in irradiated SCID mice (27). In contrast, cells from Peyer's patches (PP) and mesenteric lymph nodes (MLN), which belong in the same intestinal immune compartment but lack c-kit ϩ Lin Ϫ cells, failed to do so.…”
Section: N Umerous Intraepithelial T Cells (Iel)mentioning
confidence: 97%
“…RAG-2 transcripts are also detectable by RT-PCR in IEL from the small intestine but not the large intestine (25). Thus, it is important to explore not only TCR Ϫ IEL but also cells that reside in CP for the expression of RAG-1 and/or -2 genes because CP were shown to be responsible for generating IEL (27). For this purpose, we determined RAG-2 transcripts by semiquantitative RT-PCR analysis and compared mRNA of gut lymphocytes with those of thymocytes from WT and RAG-2 Ϫ/Ϫ mice, with the latter two mRNA serving as positive and negative templates, respectively.…”
Section: Tcr ϫ Iel and Cp Lymphocytes Express Rag-2 Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…These T cell precursors are c-kit ϩ , IL-7R␣ ϩ , and Thy-1 ϩ and are in close contact with CD11c ϩ dendritic cells concentrated at the periphery of the CP (1). CP are regarded as a site where extrathymic differentiation of T cells can take place, as transfer studies have demonstrated that T cell precursors isolated from CP can differentiate into mature T cells expressing ␣␤ or ␥␦ TCRs that reside in the intestinal epithelium (2). CP and intestinal intraepithelial lymphocytes (IEL) can also be reconstituted with wild-type bone marrow (BM) in athymic IL-2R common ␥-chain-deficient double mutant mice that genetically lack the thymus, CP, and IEL (3).…”
Section: Intestinal Cryptopatch Formation In Mice Requiresmentioning
confidence: 99%
“…The absence of V␤5 Ϫ CD4 SP thymocytes, even in mice in which most peripheral CD4 ϩ T cells are V␤5 Ϫ , the nontemplated nucleotide sequences in the revised TCR ␤-chain genes that are atypical of those generated in the adult thymus (18), and the kinetics of accumulation of V␤5 Ϫ CD4 ϩ peripheral T cells that remain unchanged after thymectomy (14), all point to the peripheral origin of cells undergoing TCR revision. Although extrathymic RAG expression has been reported previously in specialized tissue such as intestinal cyptopatches, it is not associated with TCR␣␤ ϩ CD4 ϩ T cells located in other secondary lymphoid tissues (45,46). The in vitro induction of GFP expression in peripheral GFP Ϫ CD4 ϩ T cells from V␤5 Tg RAG2/GFP knockin mice (Fig.…”
Section: Discussionmentioning
confidence: 98%